Assessing Response in Atopic Dermatitis: A Systematic Review of the Psychometric Performance of Measures Used in HTAs and Clinical Trials - Hannah Penton; Sayeli Jayade; Santhani Selveindran; Marieke Heisen; Christophe Piketty; Liliana Ulianov; Zarif K. Jabbar-Lopez; Jonathan I. Silverberg; Jorge Puelles (Adis, Springer Healthcare, 2023)
Abstract Introduction Assessing treatment response is key to determining treatment value in atopic dermatitis (AD). Currently, response is assessed using various clinician- or patient-reported measures and response criteria. This variation creates a mismatch of evidence across trials, hindering the ability of clinicians, regulators, and payers to compare the efficacy of treatments. This review identifies which measures and criteria are used to determine response in clinical trials and health technology assessments (HTAs). Moreover, it systematically reviews the psychometric performance of those measures and criteria to understand which perform best in capturing patient-relevant symptoms and treatment benefits. Methods A scoping review of clinical trials and HTAs in AD identified the following measures for inclusion: the Eczema Area and Severity Index (EASI), the Investigator's Global Assessment (IGA), the Dermatology Life Quality Index (DLQI) and the Peak Pruritus Numerical Rating Scale (PP-NRS). A systematic search was performed in MEDLINE and Embase to identify studies testing the psychometric performance of these measures in adults or adolescents with AD. Results A lack of consistency in the assessment of response was observed across clinical trials and HTAs. Important gaps in psychometric evidence were identified. No content validations of the EASI and IGA in AD were found, while some quantitative studies suggested that these measures fail to capture itch, a core symptom. The PP-NRS and DLQI performed well. No studies compared the performance of different response criteria. Conclusion Content validation of the PP-NRS confirmed the importance of itch as a core symptom and treatment priority in AD; however, itch is not well covered in the EASI or IGA. Including the PP-NRS in clinical trials and HTAs will better capture patient-relevant benefit and response. Although various response criteria were used, no studies compared the performance of different criteria to inform which were most appropriate to compare treatments in clinical trials and HTAs.